Dentistry and Generation Z: Aspirations of Recent Graduates - López-Santacruz, Hiram Daniel; Guízar-Mendoza, Juan Manuel (Odovtos - International Journal of Dental Sciences, 2025)
Currently, the vast majority of dental students and recent graduates belong to Generation Z (born since 1996). They have been characterized by solving problems with their creativity and the use of technological resources. It is important to be aware of their perceptions regarding their experiences, future plans and aspirations. The aim of the study was to analyze the professional aspirations of recent graduates of Dentistry, belonging to Generation Z who studied at a University in Mexico. Descriptive, observational and cross-sectional study based on a survey developed in Google Forms, consisting of questions about demographic data, professional aspirations and motivations of recent graduates of Dentistry. The database was organized in Microsoft Excel. The final data were analyzed with STATISTICS software, using the chi-square test to compare proportions of categorical variables between groups. A value of p<0.05 was considered statistically significant. The sample of 107 responses consisted of 85 females and 22 males, and the average age was 23.7 years. The most important findings were that 100% of the recent graduates planned to continue with their dental profession, the majority had plans to start a Postgraduate Program and work in private practice as owners or associates. There were statistically significant differences regarding their mobility plans, and personal growth was identified as their main motivation. The findings of the study demonstrate that the recent graduates of Dentistry belonging to Generation Z are determined to continue their professional training with great efforts to carry out a quality clinical practice for the benefit of society.